A Social Science: PENDIDIKAN IPS SEBAGAI POROS ILMU GLOBAL - Muhammad Zacky; Desy Safitri; Sujarwo (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Social studies is a very important domain in education because it helps the scope of the social sciences field of knowledge to be able to understand and overcome global challenges. In the current era of globalization and complexity of world problems, social science knowledge is becoming increasingly relevant. This article will discuss how IPS can understand various global issues such as climate change, international trade, migration issues, and international conflicts. Social studies not only provides knowledge about these issues, but also teaches the analytical, critical, and problemsolving skills necessary to participate in global discussions. In addition, this article will highlight the importance of a global perspective in teaching social studies. Expert theory also emphasizes that learning social studies from a global perspective can also help increase intelligence, tolerance and cross- cultural cooperation. By understanding differences and similarities around the world, students can become more conscious global citizens and contribute to solutions to global problems. In short, social studies in a global perspective is an important component in education that helps students understand global issues, develop analytical skills, and encourage cross-cultural understanding. This article will discuss the importance of social studies in the context of globalization and how teaching social studies can help students become more informed world citizens and engage in global issues. Keywords : Global Issues, Expert Theory, Social Studies. Ilmu Pengetahuan Sosial merupakan ranah yang sangat penting dalam pendidikan karena membantu lingkup bidang ilmu dari IPS mampu memahami dan mengatasi tantangan global. Pada era globalisasi dan kompleksitas masalah dunia saat ini, pengetahuan IPS menjadi semakin relevan. Artikel ini akan membahas bagaimana IPS dapat memahami berbagai isu global seperti perubahan iklim, perdagangan internasional, isu migrasi, dan konflik internasional. IPS tidak hanya memberikan pengetahuan tentang isu-isu ini, tetapi juga mengajarkan keterampilan analisis, kritis, dan pemecahan masalah yang diperlukan untuk berpartisipasi dalam diskusi global. Selain itu, artikel ini akan menyoroti pentingnya perspektif global dalam pengajaran IPS. Teori ahli juga menekankan bahwa pembelajaran IPS dalam perspektif global juga dapat membantu mempromosikan kecerdasan, toleransi, dan kerja sama lintas budaya. Dengan menguatkan literasi ilmiah mengenai memahami perbedaan dan kesamaan di seluruh dunia, seseorang dapat menjadi warga dunia yang lebih sadar dan berkontribusi pada solusi masalah global. Dalam ringkasan, IPS adalah wawasan global dengan komponen penting dalam bidang ilmu yang membantu seluruh manusia dalam memahami isu-isu global, mengembangkan keterampilan analitis, dan mendorong pemahaman lintas budaya. Artikel ini akan membahas pentingnya IPS dalam konteks globalisasi dan bagaimana pengajaran IPS dapat membantu siswa menjadi warga dunia yang lebih terinformasi dan terlibat dalam isu-isu global. Kata Kunci : Isu Global, Teori Ahli, IPS